Artemisia Annua L. Infusion Consumed Once a Week Reduces Risk of Multiple Episodes of Malaria: A Randomised Trial in a Ugandan Community - Ogwang, Patrick E.; Ogwal, Jasper O.; Kasasa, Simon; Olila, Deogratius; Ejobi, Francis; Kabasa, David; Obua, Celestino (Tropical Journal of Pharmaceutical Research, 2012)
To evaluate the protective effect of Artemisia annua infusion against malaria in a community that uses it as herbal ‘tea’ for malaria prevention. Methods: 132 flower farm workers who met the study inclusion criteria and were not yet using A. annua infusion were randomized either to A. annua or placebo groups in the ratio of 1:1. Treatments were administered once a week under direct observation to participants. Malaria episodes were documented over a 9-month period while adverse effects were documented over 12 months. Results: A. annua herbal ‘tea’ significantly reduced the risk of suffering more than one episode of malaria in nine months by 55 % (12/67 vs 26/65, p = 0.005 No participant experienced any serious adverse effect although bitter taste was the most common side effect of the infusion. Conclusion: Artemisia annua infusion consumed once a week was effective in preventing multiple episodes of malaria in humans living in malaria endemic areas. However, its bitter taste and the risk of development of malaria parasite resistance to the artemisinin contained in it remain major challenges for its use in the mass control of malaria.
Keywords: Artemisia annua; Herbal tea; Community; Malaria prevention